From Kitchen to Cloud: Enabling Women’s Innovation through Frugal Tech and Policy Support - M, Zaheer Ahmed (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
In the digital age, even the most informal and home-based skills can be transformed into scalable, income-generating ventures through the strategic use of frugal technology and government-backed policy interventions. This paper explores how housewives and women from non-traditional work backgrounds can evolve into successful entrepreneurs by embracing low-cost digital tools and leveraging schemes such as MUDRA Yojana, PMEGP, Stand-Up India, and digital literacy initiatives. The study presents a multidimensional framework that integrates mobile-based applications, social media marketing, online marketplaces, and basic AI-powered tools with existing household skills ranging from cooking and tailoring to craftwork and tutoring. Case studies from rural and semi-urban India illustrate how women have transitioned from kitchen-centered activities to cloud-based enterprises, achieving both economic empowerment and social recognition. The paper emphasizes the role of digital inclusion, skill-based microlearning, and local ecosystem support in fostering sustainable, women-led innovation at the grassroots level. It concludes by recommending actionable strategies for policy enhancement and capacity-building to bridge the digital gender divide and fuel inclusive growth.